2021
DOI: 10.1073/pnas.2025451118
|View full text |Cite
|
Sign up to set email alerts
|

A membrane protein display platform for receptor interactome discovery

Abstract: Cell surface receptors are critical for cell signaling and constitute a quarter of all human genes. Despite their importance and abundance, receptor interaction networks remain understudied because of difficulties associated with maintaining membrane proteins in their native conformation and their typically weak interactions. To overcome these challenges, we developed an extracellular vesicle-based method for membrane protein display that enables purification-free and high-throughput detection of receptor–liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…ACE2 is reported to have a high affinity for the spike protein [6, 10]. LRRC15 is a leucin-rich repeat domain containing protein which is an orphan cancer-associated protein [25, 26]. There is no reported role of LRRC15 in SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…ACE2 is reported to have a high affinity for the spike protein [6, 10]. LRRC15 is a leucin-rich repeat domain containing protein which is an orphan cancer-associated protein [25, 26]. There is no reported role of LRRC15 in SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our inability to recombinantly produce a functional version of LRRC15 when truncating its extracellular domain, we conjecture that the transmembrane domain or cytoplasmic cysteine-rich region of the protein may also be required. A recent study on LRRC15 similarly found the presence of a membrane-spanning domain was essential for binding activity to be observed (Cao et al, 2021). Despite its lack of biochemical characterization, LRRC15 is remarkably well-conserved among mammals, including being approximately 90% identical in sequence between human and nearly all proposed host species for SARS-CoV-2 (Supplemental figure 7).…”
Section: Discussionmentioning
confidence: 98%
“…To illustrate an example of a successful RDIMIS screen, we provide the raw data (Supplemental Data) for two screens reported in Cao et al. (2021). Here, we outline the steps for understanding the data produced from screening PDL1‐ and PVR‐expressing rEVs against a comprehensive library of STM ectodomains: We recommend performing at least two screens in 1 day, as we have observed day‐to‐day variations in the data. Every plate should have positive control wells (e.g., coelenterazine‐h incubated with rEVs).…”
Section: Commentarymentioning
confidence: 99%
“…Because the receptor of interest is expressed on the membranes of rEVs, RDIMIS presents two key advantages: (1) the receptor does not need to be solubilized, purified, or tagged for protein interaction discovery and (2) the receptor is presented in a more physiologically relevant membrane microenvironment in the form of rEVs, which provide diverse lipids, glycans, and cofactors. These advantages of RDIMIS allowed us to identify an interaction between two tumor markers, LRRC15 and CD248, that could not be identified outside a membrane context (Cao et al., 2021).…”
Section: Introductionmentioning
confidence: 99%